PERENCANAAN ULANG SALURAN DRAINASE BERWAWASAN LINGKUNGAN PADA JALAN RAYA PENATARAN KABUPATEN BLITAR - Oktavia, Anisa Gita; Charits , Moh.; Sutikno (Prokons: Jurnal Teknik Sipil, 2024)
The drainage channel on Jalan Raya Penataran cannot function properly due to rainwater runoff on the road causing flooding and disrupting community activities. This is due to the condition of the drainage channel which is damaged and not maintained so that it cannot accommodate the existing discharge. The purpose of this research is to evaluate drainage channels, calculate design rainfall, determine the dimensions of new channels and supporting buildings, plan the use of biopores as an application of environmentally sound drainage, and calculate a cost budget plan. This research implemented three types of data sources, namely data on the unit price of work of Blitar Regency in 2024, topographic maps, and rainfall data at three nearby stations (Karangnongko, Pojok, Ngadirejo). The methods implemented to process the research data included the rational method to analyse the design flood discharge, the chi square and Smirnov-kolmogorov methods with a 10-year return period to analyse suitability, and the log pearson type III method to analyse rainfall data. Based on the analysis and data processing carried out, 0.025 - 0.133 m3 per second was found as the design flood discharge. Then the drainage system made is 9567 pieces with a depth of 1 metre and an infiltration hole diameter of 100 cm. This drainage system prioritises environmental insights. Furthermore, the dimensions of the channel made have the largest diameter of 0.80 m x 1.00 m and 0.24 m x 0.43 m as the smallest diameter. While the required construction implementation is IDR 1,413,034.00.